2013
DOI: 10.1007/s10903-013-9893-6
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mental Health Status of Iraqi Refugees Resettled in the United States

Abstract: Background We conducted a survey among Iraqi refugees resettled in the United States to assess their physical and mental health status and healthcare access and utilization following the initial eight month, post-arrival period. Methods We randomly selected Iraqi refugees: ≥18 years of age; living in the United States for 8 to 36 months; and residents of Michigan, California, Texas and Idaho. Participants completed a household questionnaire and mental health assessment. Results We distributed 366 surveys. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 25 publications
3
114
0
5
Order By: Relevance
“…In comparison to other studies about refugees from Syria [12,13,14] and Iraq [15,16], we found consistent results. Compared to studies from Germany [17,18,19], we found similar or higher levels of mental distress.…”
Section: Discussionsupporting
confidence: 84%
“…In comparison to other studies about refugees from Syria [12,13,14] and Iraq [15,16], we found consistent results. Compared to studies from Germany [17,18,19], we found similar or higher levels of mental distress.…”
Section: Discussionsupporting
confidence: 84%
“…Of these, the need for translation assistance, medical care, and dental care never dropped below 87%. Upon arrival to the U.S., refugees currently are provided 8 months of subsidized health and dental insurance [19], yet Iraqi refugees frequently lacked access to medical care in Iraq and, thus, often have poor health upon entering the U.S. [6]. As such, their health care and dental needs appear to require more than 8 months of coverage in the U.S.…”
Section: Discussionmentioning
confidence: 99%
“…Previous cross-sectional research has found that refugees report a high need for physical and mental health care [48], financial support [5,7], translation/language assistance [6,8], and aid in securing safe housing [3]. Throughout this article we refer to these as institutional resources .…”
Section: Determinants Of Resource Needs and Utilization Among Refugeementioning
confidence: 99%
“…While refugees come from all over the globe, they universally struggle with chronic illnesses [37], mental health issues [38], untreated infectious diseases [39], nutrition-related diseases [40], substance abuse [41], and a comorbid combination of any of these conditions [42]. Refugees are further disadvantaged by having less access to necessary healthcare in their countries of origin that impact acquired causes of infertility, such as antibiotic treatments for sexually transmitted infections and corrections of fistulas that occur during and/or after unattended childbirth [43].…”
Section: Infertility Treatment and Refugeesmentioning
confidence: 99%